Experiences of Intimate Partner and Neighborhood Violence and Their Association With Mental Health in Pregnant Women. Issue 6 (March 2018) - Barcelona de Mendoza, Veronica; Harville, Emily W.; Savage, Jane; Giarratano, Gloria
Both intimate partner violence and neighborhood crime have been associated with worse mental health outcomes, but less is known about cumulative effects. This association was studied in a sample of pregnant women who were enrolled in a study of disaster exposure, prenatal care, and mental and physical health outcomes between 2010 and 2012. Women were interviewed about their exposure to intimate partner violence and perceptions of neighborhood safety, crime, and disorder. Main study outcomes included symptoms of poor mental health; including depression, pregnancy-specific anxiety (PA), and posttraumatic stress disorder (PTSD). Logistic regression was used to examine predictors of mental health with adjustment for confounders. Women who experienced high levels of intimate partner violence and perceived neighborhood violence had increased odds of probable depression in individual models. Weighted high cumulative (intimate partner and neighborhood) experiences of violence were also associated with increased odds of having probable depression when compared with those with low violence. Weighed high cumulative violence was also associated with increased odds of PTSD. This study provides additional evidence that cumulative exposure to violence is associated with poorer mental health in pregnant women.